Navigating forced migration in the Horn of Africa: a systematic review of IGAD’s strategic challenges and opportunities - Frank Ahimbisibwe; Cedric M. Nkiko (Cogent Social Sciences, 2025)
This systematic review examines how the Intergovernmental Authority on Development (IGAD) has responded to forced migration in the Horn of Africa, focusing on the legal, economic, and humanitarian challenges affecting its capacity for coordinated action. The review includes 22 studies published after 1995 that evaluate IGAD’s legal and policy frameworks, regional initiatives, and implementation practices. Sources were identified through systematic searches of Scopus, JSTOR, and Google Scholar, as well as official IGAD reports and regional policy documents retrieved in February and March 2025. Studies were screened for thematic relevance and geographic focus, and a qualitative thematic synthesis was used to identify core patterns. The analysis shows that IGAD has initiated meaningful regional frameworks, including the Nairobi, Kampala, and Djibouti Declarations, but the impact of these instruments is undermined by fragmented national legal systems that remain largely non-binding. As a result, displaced persons continue to face barriers to accessing basic rights such as employment, education, and freedom of movement. Financial constraints, infrastructure deficits, and inconsistent humanitarian coordination further impede effective responses. Many studies highlight the lack of inclusive, participatory mechanisms in both planning and delivery, especially in relation to vulnerable groups. While data limitations and methodological heterogeneity are acknowledged, the review identifies strategic pathways forward, including harmonisation of legal standards, investment in sustainable funding mechanisms, and strengthening of cross-border coordination through participatory governance.
Keywords: Intergovernmental Authority on development; UNHCR; Horn of Africa; forced migration; refugees; asylum seekers; internally displaced persons